Multi-locus phylogenetic analyses support the monophyly and the Miocene diversification of Iksookimia (Teleostei: Cypriniformes: Cobitidae). Issue 1 (2nd January 2018) - Kwan, Ye-Seul; Kim, Daemin; Ko, Myeong-Hun; Lee, Wan-Ok; Won, Yong-Jin
Abstract : The genus Iksookimia contains six species of primary freshwater fishes that are endemic to South Korea. Previous phylogenetic studies, based on DNA sequence data from three or fewer loci, have suggested non-monophyly of the genus, providing inconsistent resolutions of the relationships of Iksookimia . Our coalescent and concatenation-based phylogenetic analyses, utilizing seven unlinked nuclear-encoded genes, strongly supported Iksookimia as a monophyletic group, emphasizing the importance of multi-locus data in investigating complicated phylogenetic relationships. A relaxed molecular clock analysis using fossil calibrations, indicated that the origin of the major lineages of Iksookimia occurred between ∼12 to 5 Ma, which is consistent with the Miocene uplift of the Taebaek and Sobaek Mountains and the Miocene activation of the major south-eastern faults. These palaeogeographic events may have served as vicariant events in the diversification of Iksookimia .